Drylot Backgrounding of Beef - Dhuyvetter, Kevin C.; Langemeier, Michael (My University, 2011)
This publication helps producers that have a drylot backgrounding enterprise, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF600_2011_01
Keywords: MF600; Economics; Livestock; MF